Hypertriglyceridemic waist phenotype: Association with initial neurological severity and etiologic subtypes in patients with acute ischemic stroke - Ren, Yuan; Qiu, Zi-Han; Wu, Wei-Hua; Dong, Xiao-Guang; Han, Shuang; Zhang, Fu-Liang; Kong, Fan-Li; Li, Feng-E (Frontiers in Endocrinology, 2022)
Objective To explore the relationship of hypertriglyceridemic waist phenotype (HTWP) with initial neurological severity and etiologic subtypes in patients with acute ischemic stroke. Methods The data for this study were collected from hospitalized patients within 72 h of acute ischemic stroke onset at the Department of Neurology of the Affiliated Hospital of Beihua University from 1 July 2020 to 30 June 2022. The initial neurological severity was assessed by the National Institute of Health Stroke Scale (NIHSS) on the day of admission: NIHSS <6 was defined as mild stroke, and NIHSS ≥6 as moderate to severe stroke. HTWP was defined by fasting serum triglycerides ≥1.7 mmol/L and waist circumference ≥90 cm in men and ≥80 cm in women. Differentiation of etiologic subtypes was based on the method reported in the Trial of Org 10 172 in Acute Stroke Treatment. Multivariate logistic regression analysis was used to analyze the association of HTWP with initial neurological severity and etiologic subtypes. Results The study included 431 patients. Compared with the normal waist–normal blood triglyceride group, patients with HTWP had reduced risks of moderate to severe stroke [odds ratio (OR): 0.384, 95% confidence interval (CI): 0.170–0.869; P = 0.022]. In addition, the risk of small-artery occlusion stroke was 2.318 times higher in the HTWP group than in the normal triglyceride–normal waist (NWNT) group (OR: 2.318, 95% CI: 1.244–4.319; P = 0.008). Conclusion Initial neurological severity was less severe in patients with HTWP, and HTWP was associated with an increased risk of small-artery occlusion stroke.